The Density and Length of Root Hairs Are Enhanced in Response to Cadmium and Arsenic by Modulating Gene Expressions Involved in Fate Determination and Morphogenesis of Root Hairs in Arabidopsis - Bahmani, Ramin; Kim, Dong G.; Kim, Jin A.; Hwang, Seongbin (Frontiers in Plant Science, 2016)
Root hairs are tubular outgrowths that originate from epidermal cells. Exposure of Arabidopsis to cadmium (Cd) and arsenic [arsenite, As(III)] increases root hair density and length. To examine the underlying mechanism, we measured the expression of genes involved in fate determination and morphogenesis of root hairs. Cd and As(III) downregulated TTG1 and GL2 (negative regulators of fate determination) and upregulated GEM (positive regulator), suggesting that root hair fate determination is stimulated by Cd and As(III). Cd and As(III) increased the transcript levels of genes involved in root hair initiation (RHD6 and AXR2) and root hair elongation (AUX1, AXR1, ETR1, and EIN2) except CTR1. DR5::GUS transgenic Arabidopsis showed a higher DR5 expression in the root tip, suggesting that Cd and As(III) increased the auxin content in the root tip. Knockdown of TTG1 in Arabidopsis resulted in increased root hair density and decreased root hair length compared with the control (Col-0) on 1/2 MS media. This phenotype may be attributed to the downregulation of GL2 and CTR1 and upregulation of RHD6. By contrast, gem mutant plants displayed a decrease in root hair density and length with reduced expression of RHD6, AXR2, AUX1, AXR1, ETR1, CTR1, and EIN2. Taken together, our results indicate that fate determination, initiation, and elongation of root hairs are stimulated in response to Cd and As(III) through the modulation of the expression of genes involved in these processes in Arabidopsis.